DicomFlow: gateway assíncrono e descentralizado para formação de uma infraestrutura de informação para distribuição de imagens médicas - Araújo, Danilo Alexandre Barbosa de (2017)
Digitalization of medical images, the PACS/DICOM model and advances of information and communication technologies provide the conditions to form an infrastructure for a large scale distribution of medical images. However, even considering the large installed base of PACS/DICOM, the formation of a common information infrastructure for the exchange of medical images between health organizations is not observed, as the inertia of the installed base hinders its development. An information infrastructure offers a space for information sharing and collaboration that allows the spontaneous association of people, organizations and technological components located in different geographical contexts for the development of an activity. The aim of this study was to develop the DicomFlow, an asynchronous, asymmetric and decentralized gateway, built over the PACS/DICOM installed base and e-mail infrastructure of the Internet aiming to promote the formation of an information infrastructure for distribution medical imaging, favoring the radiological work practice. Therefore, it was specified a communication protocol that supports DICOM management services based on massages exchanges and transmission of medical images, built in a modular architecture. Experiments in simulated and real environment were conducted to preliminarily assess the infrastructure as its technical and operational feasibility. It was concluded that the DicomFlow enables the exchange of images between professionals and any health organizations, provided that they belong to the installed base, promoting the formation of an information infrastructure for distribution of medical images.